Absence of germline mutations in BAP1 in sporadic cases of malignant mesothelioma - Sneddon, S.; Leon, J.; Dick, I.; Cadby, G.; Olsen, N.; Brims, F.; Allcock, R.; Moses, Eric; Melton, P.; de Klerk, N.; Musk, A.; Robinson, B.; et al. (2015)
Malignant mesothelioma (MM) is a uniformly fatal tumour caused predominantly by exposure to asbestos. It is not known why some exposed individuals get mesothelioma and others do not. There is some epidemiological evidence of host susceptibility. BAP1 gene somatic mutations and allelic loss are common in mesothelioma and recently a BAP1 cancer syndrome was described in which affected individuals and families had an increased risk of cancer of multiple types, including MM. To determine if BAP1 mutations could underlie any of the sporadic mesothelioma cases in our cohort of patients, we performed targeted deep sequencing of the BAP1 exome on the IonTorrent Proton sequencer in 115 unrelated MM cases. No exonic germline BAP1 mutations of known functional significance were observed, further supporting the notion that sporadic germline BAP1 mutations are not relevant to the genetic susceptibility of MM.